CONVENTIONAL OCCLUSION THERAPY FOR AMBLYOPIA AFTER THE AGE OF 9 YEARS-A SHORT TERM OBSERVATIONAL STUDY (International Journal of Scientific Research and Management (IJSRM), 2015)
The word Amblyopia is of Greek origin, literally means dullness of vision or rather a lack of vision but not total blindness. It is defined as unilateral or bilateral decrease of visual acuity caused by pattern vision deprivation or abnormal binocular interaction without a detectable organic cause in the eye, reversible by theraph in most appropriate cases.